Evaluasi Kinerja Akademik Fakultas Ilmu Pendidikan Universitas Negeri Makassar - Syamsul Bachri Thalib (Neutrino, 2018)
This study aim to determine the academic performance of the study program at the Faculty of Education State University of Makassar, covering (a) the implementation of learning (attendance of lecturers,student attendance, lecture materials), (b) the implementation of academic advisory tasks, (c) the implementation of the advisory thesis, (d) the availability and type of learning infrastructure and facilities, (e) improvement of qualifications and competence of lecturers and education personnel: and (f) student service and student achievement. Data collection techniques include (a) documentation, used to collect data on learning, academic, and thesis, lecturer and student conditions, achievement of lec turers and students, (b) interviews, used to collect data on students activities and students academic achievement, and (c) observation, used to collect data on campus facility and environment conditions. The result of data analysis shows that (a) the implementation of the learning is done well, (b) the implementation of academic supervisor’s job is done well, (c) the supervisor of the final project/ student thesis follow the procedure as it should, but found some thesis tha plagiarism is suspected in some programs, (d) availability of academic facilities and infrastructure is sufficient, but maintenance of campus cleanliness and beauty still needs to be improved (e) qualified and competence of lecturers quite well, (f) ratio of lecturer and student in certain study program less ratio, (g) achievement of lecturer, student, ang student affairs achievement well.